Improvement of interfacial contact for efficient PCBM/MAPbI3 planar heterojunction solar cells with a binary antisolvent mixture treatment. (6th September 2021) - Chandel, Anjali; Wu, Jia-Ren; Thakur, Diksha; Kassou, Said; Chiang, Shou-En; Cheng, Kai-Jen; Li, Chung-Yu; Yen, Yung-Sheng; Chen, Sheng-Hui; Chang, Sheng Hsiung
Abstract: Atomic-force microscopic images, x-ray diffraction patterns, Urbach energies and photoluminescence quenching experiments show that the interfacial contact quality between the hydrophobic [6, 6]-phenyl-C61 -buttric acid methyl ester (PCBM) thin film and hydrophilic CH3 NH3 PbI3 (MAPbI3 ) thin film can be effectively improved by using a binary antisolvent mixture (toluene:dichloromethane or chlorobenzene:dichloromethane) in the anti-solvent mixture-mediated nucleation process, which increases the averaged power conversion efficiency of the resultant PEDOT:PSS (P3CT-Na) thin film based MAPbI3 solar cells from 13.18% (18.52%) to 13.80% (19.55%). Beside, the use of 10% dichloromethane (DCM) in the binary antisolvent mixture results in a nano-textured MAPbI3 thin film with multicrystalline micrometer-sized grains and thereby increasing the short-circuit current density and fill factor (FF) of the resultant solar cells. It is noted that a remarkable FF of 80.33% is achieved, which can be used to explain the stable photovoltaic performance without additional encapsulations.